2019
DOI: 10.1016/j.jhydrol.2019.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater recharge, flow and stable isotope attenuation in sedimentary and crystalline fractured rocks: Spatiotemporal monitoring from multi-level wells

Abstract: The complexities of fractured rock systems necessitate the use of multi-level monitoring wells for the measurement of isotopic tracers with depth. These methods, however, are rarely employed in groundwater flow studies, particularly involving temporal isotope measurements in multiple rock types. To understand the use of isotopic snowmelt tracers for exploring surface connections and recharge, an investigation was undertaken at three geologically-distinct field sites in south-eastern Ontario, Canada. Results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…The selection of specific methods depends on several factors such as the objective of the study, the consideration given to spatial and temporal scales and variability of the considered processes, the characteristics of the aquifer, and the availability of hydro-climatic data [15,30]. However, a reliable characterization of the aquifer recharge mechanism might help in developing a robust conceptualization of the recharge process [17,18,31,32] and support the development of aquifer protection policies [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…The selection of specific methods depends on several factors such as the objective of the study, the consideration given to spatial and temporal scales and variability of the considered processes, the characteristics of the aquifer, and the availability of hydro-climatic data [15,30]. However, a reliable characterization of the aquifer recharge mechanism might help in developing a robust conceptualization of the recharge process [17,18,31,32] and support the development of aquifer protection policies [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Other than that, it can be influenced by geological control, and the result cannot be validated accurately. Studies using a water stable isotope method found that the results could be verified more accurately than the other techniques, as Darling stated [7]- [9].…”
Section: Methodsmentioning
confidence: 99%
“…Sharp rises in hydraulic head corresponding to decreases in groundwater temperature indicate that rapid midwinter recharge can occur despite the presence of thin basal ice (1-2.5 cm) and shallow (<10 cm) frozen ground. The considerable decreases in groundwater temperature (up to 4℃, Figure 3c) during recharge events indicates that cold water from snowmelt or winter rain is being transported advectively from surface along relatively short preferential flow paths (Gleeson et al, 2009;Wright and Novakowski, 2019). Less temperature sensitivity in the well would be evidence of longer flow paths, as more heat is transferred from the soil or rock matrix to the cold infiltrating water (Bou Jaoude et al, 2018).…”
Section: Mechanisms Of Winter Recharge In Fractured Rockmentioning
confidence: 99%
“…This is despite bedrock aquifers in seasonally frozen environments providing, in some areas, nearly all municipal drinking water (Golder Associates Ltd., 2003;Nunes et al, 2017;Singer et al, 2003) and sustaining low-flows for ecologically sensitive habitats (Levison et al, 2014). Unlike unconsolidated aquifers, the low storativity of bedrock aquifers and high sensitivity to surface conditions can limit the capacity to buffer climatic changes (Cai and Ofterdinger, 2016;Hugman et al, 2012;Rathay et al, 2018;Wright and Novakowski, 2019). This leaves shallow bedrock aquifers particularly susceptible to impacts from climate change, especially in areas where winter precipitation is a dominant source of recharge.…”
Section: Introductionmentioning
confidence: 99%